Identification and Validation of an Immune and Ferroptosis-Combined Index for Non–Small Cell Lung Cancer - Teng, Yang; Wang, Bo; Shang, Desi; Yang, Ning (Frontiers in Genetics, 2021)
Background: Non-small cell lung cancer (NSCLC) is among the major health problems around the world. Reliable biomarkers for NSCLC are still needed in clinical. We aim to develop a novel ferroptosis and immune-based index for NSCLC. Methods: The training and testing datasets were obtained from TCGA and GEO database, respectively. Immune- and ferroptosis-related genes were identified and used to establish a prognostic model. Then, the prognostic and therapeutic potential of the established index were evaluated. Results: Intimate interaction of immune genes with ferroptosis genes was observed. A total of 32 prognosis-related signatures were selected to develop a predictive model for NSCLC using LASSO Cox regression. Patients were classified into the high and low risk group based on the risk score. Patients in low-risk group have better OS in contrast with that in high-risk group in independent verification datasets. Besides, patients with high-risk score have shorter OS in all subgroups (T, N and M0 subgroups) and pathological stages (Stage I, II and III). The risk score was positively associated with ImmuneScore, StromalScore and FerroptosisScore in TCGA, as well as GEO cohorts. A different immune cells infiltration between the high risk and the low-risk groups was also observed. Finally, we explored the significance of our model in tumor related pathways and different enrichment levels in therapeutic pathway were observed between high and low-risk groups. Conclusion: The present study developed an immune and ferroptosis combined index for prognosis of NSCLC.